Dimensiones y características nutritivas de las bellotas de los Quercus de la dehesa - Rodríguez-Estévez, V; García Martínez, A; Mata Moreno, C; Perea Muñoz, J M; Gómez Castro, A G (Arch. Zootec, 2008)
Acorns production of Quercus (Q. ilex, Q. suber, etc.) is an important feeding resource in the dehesa during autumn-winter. Acorn weight, size and shape present a lot of variability between species, species, individuals and areas. Also composition is variable and is influenced by its own maturation process and external agents (humidity, parasites, etc.). Op.osite, shell and cotyledons proportions show higher homogeneity. Shell composition has a very high level of tannins and lignin, which affects its digestibility. Kernel has a very high level of glucids (80% of DM) and lipids (5-10% of DM) with a oleic acid content up.er 60%, however protein level is very low (4-6% of DM). Many wild and domestic species eat acorns; however, in the dehesa, acorns are used to feed fattening Iberian pigs because this breed is the single one capable of peeling them and rises a high commercial value
Keywords: fatty acids; iberian pig; Montanera; Quercus ilex; Quercus suber; Sus scrofa

Producción de bellota en la dehesa: factores influyentes - Rodríguez-Estévez, V; García, A; Perea, J; Mata, C; Gómez, A G (Arch. Zootec, 2007)
This paper reviews the state-of-the- knowledge of acorn production in the South- Western Iberian dehesas. In the first part are briefly described the soil and climatic determining factors and phenology of most common trees of genus Quercus at the dehesa (Q. ilex, Q. suber and Q. faginea). In the second part, acorn production estimations are analyzed. Was established a mean acorn yield of 300 to 700 kg/ ha; with individual productions of 8-14 kg/tree for Q. ilex, 5-10 kg/tree for Q. suber and 1-11 kg/ tree for Q. faginea; with a highly variable production, both between and within years and individual trees. Finally we review the factors affecting acorn production, describing density of trees (estimated in 20-50 trees/ha), masting phenomenon (with cycles of 2-5,5 years and asynchrony between trees), individual cha- racteristics of trees (genetic potential, age, top surface, etc.), tree mass handling (with favourable effect of tilling, moderate pruning and sustainable grazing), meteorological conditions (mainly drought and meteorology during flowering) and sanitary status (Lymantria, Tortrix, Curculio, Cydia, Balaninus and Brenneria).
Keywords: Agro forestry system; evergreen oak; iberian pig; Mast-seeding; Montanera; Quercus